2004
DOI: 10.1073/pnas.0401675101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic isotope effects in Ras-catalyzed GTP hydrolysis: Evidence for a loose transition state

Abstract: A remote labeling method has been developed to determine 18 O kinetic isotope effects (KIEs) in Ras-catalyzed GTP hydrolysis. Substrate mixtures consist of 13 C-depleted GTP and [ 18 O, 13 C]GTP that contains 18 O at phosphoryl positions of mechanistic interest and 13 C at all carbon positions of the guanosine moiety. Isotope ratios of the nonvolatile substrates and products are measured by using a chemical reaction interface͞isotope ratio mass spectrometer. The isotope effects are 1.0012 (0.0026) in the ␥ non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 55 publications
5
59
0
Order By: Relevance
“…Subsequently, the distance between UDP and the anomeric carbon determined from this structure might also be an over-or under-estimation. These suggested that the C-O bond to the leaving group was almost broken and that there was asymmetric hydrogen bonding or partial protonation of the leaving group oxygen (or possibly delocalization/non-bridging oxygen protonation 42 ) at an early stage. Such hydrogen-bonding/protonation of the leaving group was again consistent with the observation of hydrogen bonding in the crystal structure of the ternary complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the distance between UDP and the anomeric carbon determined from this structure might also be an over-or under-estimation. These suggested that the C-O bond to the leaving group was almost broken and that there was asymmetric hydrogen bonding or partial protonation of the leaving group oxygen (or possibly delocalization/non-bridging oxygen protonation 42 ) at an early stage. Such hydrogen-bonding/protonation of the leaving group was again consistent with the observation of hydrogen bonding in the crystal structure of the ternary complex.…”
Section: Discussionmentioning
confidence: 99%
“…With a phosphate leaving group, negative charge delocalization to the non-bridging oxygens or protonation instead on these non-bridging oxygens may also contribute to the observed lowering of the 18 O leaving group KIE. 42 It may be that protonation and charge delocalization competed for the electron density liberated by the bond cleavage and the KIE of 1.024 determined here reflected both contributions, protonation and charge delocalization. Partial protonation (which was estimated to be less than 50% from the observation of Bronsted and Taft relationships, see below) appeared also to be consistent with the structure of the ternary complex and the model that hydrogen bonding between leaving group and nucleophile guides the latter to the same face as the former 22 .…”
Section: Kinetic Analysis Of the Donor Substratementioning
confidence: 99%
“…The results were interpreted as caused by electron charge shift towards the b-phosphate due to enzyme binding, i.e. a charge distribution close to the product state [8,11]. This seems to be a common feature of proteins of the Ras superfamily, as for example tr-FTIR measurements of the RapAERapGAP complex demonstrate a similar behaviour [12].…”
Section: Introductionmentioning
confidence: 99%
“…These residues are near the ␥-phosphate and oxygen atom that bridges the ␤-and ␥-phosphate groups in GTP. The dissociative-like reaction mechanism observed in the presence and absence of GAP (22,23) requires accumulation of negative charge at the ␤-␥-bridging oxygen atom of GTP in the transition state of the hydrolysis reaction (24). Stabilization of this charge in the GAP-catalyzed reaction is aided by the arginine finger (Arg 789 ), which GAP inserts in the active site, and the ordering of both switch I and switch II at the Ras/RasGAP interface (9).…”
mentioning
confidence: 99%